Epidemiology, Transmission And Isolation Of Nipah Virus In Large Fruit Bats (Pteropus Species)In Peninsular Malaysia - Abd Rahman, Sohayati (2009)

(untitled)
Bats of the genus Pteropus are considered the natural reservoir hosts for NiV and other henipaviruses. The present study was carried out to investigate the epidemiology of NiV in Pteropus sp. in Malaysia. The specific objectives of this study are to describe the geographical distribution and population characteristics of Pteropus spp. in the peninsular, describe the geographical extent of NiV antibody in pteropid bats in the peninsular, identify the risk factors associated with the infection, determine the natural route of NiV excretion, transmission and serological patterns of the infection in captured Pteropus, estimate the seroprevalence and incidence rate of NiV seroconversion in the bats and investigate the possibility of viral recrudescence in naturally infected bats and in experimentally NiV immuno-suppressed seropositive bats P. vampyrus and P. hypomelanus were found throughout Peninsular Malaysia. P. hypomelanus inhabits the islands surrounding the peninsular while P. vampyrus were found on the mainland. P. vampyrus was extremely sensitive even to low-level human activities. Physically, P. vampyrus was significantly bigger and heavier than P. hypomelanus. The physical characteristics of bats of both species differ significantly given age and sex. Both species had similar breeding pattern throughout the year. The seroprevalence of NiV in P. hypomelanus and P. vampyrus were 11% and 32.5%, respectively. The odds ratio of seropositive for NiV was higher in P. vampyrus compared to P. hypomelanus. A repeated cross-sectional study show that NiV seroprevalence in a single population of P. hypomelanus ranged between 1% and 20%. The seroprevalence was found associated with time and the reproductive status of female bats. The bats that were either pregnant, lactating, carrying or nursing a pup were at a significantly higher risk to be seropositive when compared to dry bats. A prospective study on the bats revealed at least 5 basic serological patterns: i) High Static Positive, ii) Low Static Positive, iii) Waned-off, iv) Waned-off and Rising and v) Static Negative. Passive immunity to NiV of pup born to seropositive dam was detected for a period of up to a year. This suggests that the maternal antibody against NiV may last up to a year in captive bats. The isolation of the virus from a bat’s urine from ‘Waned-off and Rising’ antibody pattern provides for the first time, the objective evidence of the possible viral recrudescent in Pteropus bats. The virus was excreted in very low concentration and in a very short time period. This indicates that a very narrow window exist where NiV is shed by bats in the wild. The seroconvertion of another two bats within a month after the virus isolation suggests the possibility of horizontal transmission within the colony. The NiV incidence rate for seroconversion was 486 per 1000 bat-year. Stress in seropositive bats induced chemically resulted in an increased neutrophil and decrease in lymphocytes count. However, no virus was discovered from samples collected during the experiment and from organs at the end of the study. The findings from the study have contributed significantly to the understanding on the distribution of NiV among healthy Pteropus bats, transmission and persistency of the virus within the colony, and the basic bat immune response due to NiV infection